Deciphering the mitochondrial genome of Hemerocallis citrina (Asphodelaceae) using a combined assembly and comparative genomic strategy - Zhang, Kun; Wang, Yiheng; Zhang, Xun; Han, Zhiping; Shan, Xiaofei (Frontiers in Plant Science, 2022)
Hemerocallis citrina is a perennial herbaceous plant that is dedicated to mothers in Chinese culture and is widely distributed across the country. As a popular species with a long history of cultivation and utilization, it is renowned for its remarkable edible and medicinal value. In this study, we integrated Illumina short-read and Oxford Nanopore long-read sequencing to generate a complete mitochondrial genome (mitogenome) assembly of H. citrina. The H. citrina mitogenome has a multiple chromosomal structure consisting of three circular molecules that are 45,607 bp, 239,991 bp, and 182,864 bp long. We correspondingly annotated 66 genes, comprising 45 protein-coding genes (PCGs), 17 tRNA genes, and 4 rRNA genes. Comparative analysis of gene organization indicated that six syntenic gene clusters were conserved in the mitogenomes of the compared plants. The investigation of repeat content revealed repeat-rich nature of the H. citrina mitogenome, for which plentiful dispersed repeats were characterized to correlate with the size of the mitogenome. The codon usage behavior disclosed that Leucine (Leu) and Serine (Ser) were the most preferred amino acids in H. citrina, and nearly all of the codons with relative synonymous codon usage (RSCU) values greater than 1 showed the preference of A or T ending. Moreover, we inferred a total of 679 RNA editing sites in all mitochondrial PCGs, which presented perfect C-to-U types and tended to lead to the alteration of internal codons. Subsequent selective pressure analysis showed that the majority of the PCGs had undergone evolutionary negative selections, with atp9 in particular undergoing strong stabilizing selection, reflecting its indispensable function in mitogenomes. According to the phylogenetic analysis, H. citrina is close to the species Allium cepa (Amaryllidaceae) and Asparagus officinalis (Asparagaceae) in evolutionary terms. Overall, this project presents the first complete mitogenome of H. citrina, which could provide a reference genome for the comprehensive exploration of the Asphodelaceae family and can facilitate further genomic breeding and evolutionary research on this medicine–food homologous plant.